Transcriptome analysis of fat accumulation in 3T3-L1 adipocytes induced by chlorantraniliprole - Chen, Ge; Wang, Ge; Xu, Weidong; Xiao, Ying; Peng, Ye (Frontiers in Nutrition, 2022)
Chlorantraniliprole has been found to increase the accumulation of triglycerides (fats) in adipocytes, but the underlying molecular mechanisms were still unknown. The present study aimed to explore the molecular mechanisms of chlorantraniliprole-induced fat accumulation in 3T3-L1 adipocytes. The results of RNA sequencing (RNA-seq) showed that 284 differentially expressed genes (DEGs) were identified after treatment with chlorantraniliprole, involving 39 functional groups of gene ontology (GO) and 213 KEGG pathways. Moreover, these DEGs were significantly enriched in several key genes that regulate adipocyte differentiation and lipogenesis including Igf1, Rarres2, Nr1h3, Psmb8. In general, these results suggest that chlorantraniliprole-induced lipogenesis is attributed to a whole-gene transcriptome response, which promotes further understanding of the potential mechanism of chlorantraniliprole-induced adipogenesis.